A psycho-cultural approach to radio listening and creative production. (1st April 2013) - Breton, Hugh Ortega
This discussant piece introduces and explains a psycho-cultural approach to understanding the emotional dimensions of radio listening and creative production. It then explores the ways in which radio is unconsciously used by listeners as a tool for maintaining psychic coherency. A psycho-cultural approach is a valuable tool for research because it is specifically attuned to the emotional dimensions of radio use and programme-making in a therapeutically infused culture. It also provides a means of explaining why radio is used in particular ways, in terms of the everyday maintenance of the self. The article closes with a consideration of the meta-psychological consequences of convergence and recent developments in listening technologies. The aim of the article is to initiate a discussion with radio scholars on the utility of this approach.